Examining the Personality Traits and Empathetic Tendency Levels of Students of the Coaching Education Department - Kaya, Kazım; Erdoğan, Çağrı Hamdi; Bahadir, Ziya (Asian Journal of Education and Training, 2019)
The objective of this study is to determine the personality traits and empathetic tendency levels of students of the coaching education department. In addition to that, the empathetic tendency levels of students of the coaching education department were compared according to some characteristics. The research was conducted as a survey model. 347 students participated in the research group, who were studying at Erciyes University Department of Coaching Education, Faculty of Sport Sciences in the 2018-2019 academic year. In the study, Personal Information Form, Ten-Item Personality Inventory and Empathetic Tendency Scale were used as the data collection tools. SPSS program was used for the analysis of the data. According to the results of the study, the "compatible" personality trait of students of the coaching education department came to the fore and their empathetic tendency levels were determined at "medium level". Moreover, it was determined that there was statistically no significant difference in the empathetic tendency levels of students of the coaching education department concerning age, gender, academic grade, doing active sports, GPA, and sports branch.